2017
DOI: 10.5505/agri.2017.70370
|View full text |Cite
|
Sign up to set email alerts
|

IDIOPATHIC INTRACRANIAL HYPERTENSION WITHOUT HEADACHE: A CASE REPORT and LITERATURE REVIEW

Abstract: SummaryIn this article, a 23-year-old man who has an idiopathic intracranial hypertension (IIH) case is presented with blurred vision and diplopia, without headaches is reported. Although headache is the most common symptom seen in IIH, sometimes it may not be observed clinically. This situation is defined more in males in young and children and thin patients. Crucial point here is that they are being presented with serious visual evidence, so they must be aggressively treated.Keywords: Headache; idiopathic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 8 publications
(11 reference statements)
0
2
0
4
Order By: Relevance
“…Friedman et al [18] connected the intermittent course of the headache to the natural fluctuations in CSF pressure throughout the day. Eren et al [3] reported that the differences in ventricular compliance and the duration of increased intracranial pressure could explain the clinical differences between IIH patients with or without headaches; they performed a retrospective study of 152 children with IIH, and 14.5% of the patients had no headache.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Friedman et al [18] connected the intermittent course of the headache to the natural fluctuations in CSF pressure throughout the day. Eren et al [3] reported that the differences in ventricular compliance and the duration of increased intracranial pressure could explain the clinical differences between IIH patients with or without headaches; they performed a retrospective study of 152 children with IIH, and 14.5% of the patients had no headache.…”
Section: Discussionmentioning
confidence: 99%
“…The most common presentation of patients with idiopathic intracranial hypertension is headache, visual changes, and papilledema, which, if left untreated, may lead to permanent loss of vision [3]. The poor visual outcome is usually associated with early onset of reduced vision, optic disc hemorrhages, grade 4 papilledema, and a high body mass index [4].…”
Section: Introductionmentioning
confidence: 99%
“…La incidencia en la población general es de 0,5-2 de cada 100.000 personas/año aumentando en las mujeres jóvenes con obesidad hasta 12-20 de cada 100.000 personas/año (1,2,17,19,20,22) . La prevalencia en hombres y en niños no está clara debido a la falta de estudios epidemiológicos (1) .…”
Section: Epidemiologíaunclassified
“…La mayoría de los pacientes con HII sufren sobrepeso u obesidad y algunos experimentan un incremento de peso en los meses previos al diagnóstico (1) . Un incremento del peso igual o mayor al 5% (22) implica un aumento del riesgo de padecer la enfermedad en las personas no obesas. La obesidad contribuye a un empeoramiento de la sintomatología en pacientes en los que la PIC ha sido tratada (23) .…”
Section: Epidemiologíaunclassified
See 1 more Smart Citation